MSMEs in Emerging Markets : An Exploration of the Stage Model of E-Commerce Adoption - Kumar, Pawan; Kaur, Harpreet; Singh, Gursimranjit (Prabandhan: Indian Journal of Management, 2023)
Purpose : This paper aimed to develop a holistic e-commerce adoption model and explore the significant factors at various stages of e-commerce adoption in emerging markets in micro, small, and medium enterprises (MSMEs). Design/Methodology/Approach : A research model was developed by combining the diffusion of innovation and technological-organizational-environmental models with a staged model. A purposive sampling method was followed, and 384 MSME units were selected. A quantitative approach was used with a structured questionnaire as a research instrument. Findings : The factors that influence the adoption of e-commerce were observed in two ways; one is a sequential way where an enterprise starts with primary e-mail and, step by step, reaches the most advanced stage, which included not only online ordering but also online payment capabilities. Furthermore, while moving to advanced stages of e-commerce adoption, enterprises follow a nonsequential way, where an enterprise could skip some stages while moving to complex stages of e-commerce adoption. Research Implications : Various stakeholders would understand the barriers faced by the MSMEs in emerging markets so that necessary steps could be initiated to tackle this issue. Originality/Value : The study proposed a novel, holistic e-commerce adoption model and addressed the research gap by seeking to understand how MSMEs in India were adopting e-commerce by exploring their level and sequence of adoption.